Identifikasi Permasalahan Guru untuk Meningkatkan Mutu dan Profesionalisme - Linda Rahmawati; La Ode Amaluddin; Andrias; Surdin (Jurnal Penelitian Pendidikan Geografi, 2024)
This research was conducted regarding the phenomenon of low teacher competence and quality. The aim of this research is to find out: 1) teachers' internal and external problems; and 2) efforts to improve the quality and professionalism of teachers at Senior High School 2 Kulisusu. This research uses qualitative research methods, with research subjects being teachers. The research results show that: 1) teacher problems consist of internal problems including weak cognitive and pedagogical competence of teachers, lack of love for their profession, lack of innovation in learning methods. Meanwhile, external problems include a lack of physical facilities and infrastructure that support teaching and learning activities, inadequate compensation, especially for non-civil servantor or honorary teachers, and adjustments to curriculum change policies; and 2) Efforts that can be made with holding various workshop activities related to improving the quality of education, obtaining the latest information about the education quality improvement system, both through social media and collaboration with supervisors, involving teachers in the program Teacher Professional Education and independent training through online resources such as the Platforms Independent Teach application, as well as providing motivation and support to understand information technology.